The effects of projected climate change on crop water availability in the U.S. Caribbean. Issue 4 (4th April 2023) - Moraes, Flávia D. S.; Ramseyer, Craig; Gamble, Douglas
Abstract: Anthropogenic climate change affects small islands, and farming systems in the Caribbean are vulnerable to climate change due to their high dependence on rainfall. Therefore, this work evaluated how temperature and precipitation projections affect water crop needs in Puerto Rico and St. Croix. We used Daymet data to create a baseline climatology (1981–2010) and the Coupled Model Intercomparison Project Phase 6 (CMIP6) to create future climatologies (2041–2070 and 2071–2100). A water budget model estimated the water deficit, and the crop risk (CROPRISK) model determined crop suitability for sweet pepper, banana, and plantain. Results indicated an increase in water stress after 2041 for most of the region from June to August, except for western Puerto Rico, where it will occur from January to March. For sweet pepper, banana, and plantain, the most water-stressed season is projected to be January–July. November will be the only month during which all crops are projected to be highly suitable through the end of the 21st century. These findings suggested that Puerto Rico and St. Croix crop water stress may be more sensitive to changes in temperature than precipitation. HIGHLIGHTS: Water stress will increase in Puerto Rico and St. Croix from June to August after 2041. Crops such as sweet pepper, banana, and plantain will only be highly suitable in the U.S. Caribbean in November through the end of the 21st century. Changes in temperature have a greater influence on future water stress in Puerto Rico and St. Croix than changes in precipitation. Graphical Abstract